Unraveling the Water Sources in Comet 103P/Hartley 2 from Deep Impact Flyby Observations - L. M. Feaga; J. M. Sunshine (The Planetary Science Journal)
The Deep Impact eXtended Mission flyby of comet 103P/Hartley 2 offered a rare opportunity to study a hyperactive comet with high-cadence and high-resolution observations from a fixed vantage point. Using the high signal-to-noise data from the HRI-IR instrument, the H _2 O and CO _2 distributions in the comet’s coma are mapped and quantified over one complete rotation period, revealing two major sources of water: direct sublimation from the nucleus, and sublimation of icy grains in the coma in the antisunward direction. These icy grains contributed 25%–40% of the total water production during the 2010 perihelion passage, quantifying the source of Hartley 2’s hyperactivity. In addition, sublimation from slower-moving icy grains redeposited at the comet’s gravitational low is detectable within 5.2 km of the nucleus, accounting for a few percent of the water production. CO _2 production distinctly tracks with the nucleus’s small lobe, which is seen to be active throughout Hartley 2’s rotation even when not illuminated and thus is less dependent on instantaneous solar illumination than water. Differences in CO _2 and H _2 O sources lead to spatially resolved CO _2 /H _2 O ratios ranging from 5% to 21% sampled at various times and locations in the coma throughout a single rotation, while the global abundance ratio varies by a factor of ∼2 throughout a single rotation (6%–12%). These observations highlight the complex interaction between solar insolation, comet rotation, and volatile outgassing and suggest that the lobes of Hartley 2 may have different formational or evolutionary origins, implying large-scale mixing in the protoplanetary disk.